From "participant" to "friend": the role of Facebook engagement in ethnographic research. Issue 4 (11th September 2017) - Edirisingha, Prabash Aminda; Abarashi, Jamal; Ferguson, Shelagh; Aitken, Rob
Abstract : Purpose: The purpose of this paper is to illustrate the methodological significance and potential of integrating Facebook in ethnographic research. The authors discuss how friendly relationships with participants could be initiated, fostered and managed by incorporating Facebook in ethnographic data collection and how such relationships deepen ethnographic interpretation. Design/methodology/approach: This paper focuses on the methodological implications of adopting "friendship as method" during ethnographic research. The discussion is premised upon a longitudinal, multi-method ethnographic research process exploring new family identity formation in Sri Lanka and New Zealand. Findings: Building on friendship theories, the authors suggest that Facebook engagement helps overcome three challenges inherent to ethnographic research: gaining access and immersion, capturing multiple perspectives, and developing rich and thick interpretations. The findings illustrate that adopting Facebook as a platform to strengthen friendships with research participants expands the researcher's field by enabling him to follow the ethics and pace of conventional friendship and by inspiring dialogical interaction with participants. Thus, it is suggested that Facebook helps diluting the power hierarchy in the participant–researcher relationship and encourages participants to reveal more subtle details of their mundane lived experiences. Originality/value: Even though researchers have often used social media interactions in ethnographic research, there is no theoretical foundation to understand how such interactions could better inform the depth and richness of research phenomena. Particularly, considering the emerging significance of social media in personal identity construction, sustenance and enactment, it is import to understand how such mediums enable researchers overcome inherent methodological complexities. Therefore, this paper contributes to literature on conventional ethnography, netnography and friendship theories by presenting a theoretical framework to understand how Facebook interaction contributes to overcome challenges in conducting ethnographic research.